Effects of Hypoxia–Hyperoxia Preconditioning on Indicators of Muscle Damage After Acute Resistance Exercise in Male Athletes - Chen, Peng-Wen; Hsu, Chi-Chieh; Lai, Li-Fan; Chi, Chung-Pu; Yu, Szu-Hsien (Frontiers in Physiology, 2022)
Purpose: The purpose of this study was to investigate the effects of acute repeated hypoxia-hyperoxia preconditioning on resistance exercise (RE)-induced muscle damage in male athletes. Methods: Eleven young male athletes participated in this randomized double-blind counter-balanced crossover study, and were divided into Normoxia (N) and Hypoxia-Hyperoxia (HH) trials. Subjects of the respective trials were supplied with normoxic (FiO2=0.21), or alternating hypoxic/hyperoxic air (FiO2=0.10/0.99, 5 min each) for 60 min. Thirty min after preconditioning, subjects performed acute bouts of RE consisting of bench press, deadlift and squats. Each exercise included 6 sets of 10 repetitions at 75% one repetition maximum (1RM) with 2 min rest between sets. After a 2-week washout period, subjects changed trials and completed the same study procedure after the alternate preconditioning. Muscle soreness, maximal voluntary contraction (MVC), and circulating biochemical markers were tested before preconditioning (baseline) and during recovery at 0, 24 and 48 h after exercise. Results: Acute RE significantly increased levels of muscle soreness, creatine kinase (CK) and myoglobin (Mb), and decreased levels of peak knee extension torque in the N trial. Muscle soreness, CK and Mb levels of the HH trial were significantly lower than that of the N trial after exercise. Interestingly, interleukin-6 (IL-6) levels of the HH trial increased significantly 0 h after exercise compared to baseline, and were significantly higher than that of the N trial 0 and 24 h after exercise. However, no significant differences of thiobarbituric acid reactive substances (TBARS), cortisol, testosterone, peak torque and average power levels were found between N and HH trials during recovery. Conclusion: Our data suggest that pre-exercise treatment of alternating hypoxic/hyperoxic air could attenuate muscle damage and pain after acute RE, but has no effect on muscle strength recovery in young male athletes.